Is IQG-607 a Potential Metallodrug or Metallopro-Drug With a Defined Molecular Target in Mycobacterium tuberculosis? - Abbadi, Bruno L.; Rodrigues-Junior, Valnês da Silva; Dadda, Adilio da Silva; Pissinate, Kenia; Villela, Anne D.; Campos, Maria M.; Lopes, Luiz G. de França; Bizarro, Cristiano V.; Machado, Pablo; Sousa, Eduardo H. S.; Basso, Luiz A. (Frontiers in Microbiology, 2018)
The emergence of strains of Mycobacterium tuberculosis resistant to isoniazid (INH) has underscored the need for the development of new anti-tuberculosis agents. INH is activated by the mycobacterial katG-encoded catalase-peroxidase, forming an acylpyridine fragment that is covalently attached to the C4 of NADH. This isonicotinyl-NAD adduct inhibits the activity of 2-trans-enoyl-ACP(CoA) reductase (InhA), which plays a role in mycolic acid biosynthesis. A metal-based INH analog, Na3[FeII(CN)5(INH)]4H2O, IQG-607, was designed to have an electronic redistribution on INH moiety that would lead to an intramolecular electron transfer to bypass KatG activation. HPLC and EPR studies showed that the INH moiety can be oxidized by superoxide or peroxide yielding similar metabolites and isonicotinoyl radical only when associated to IQG-607, thereby supporting redox-mediated drug activation as a possible mechanism of action. However, IQG-607 was shown to inhibit the in vitro activity of both wild-type and INH-resistant mutant InhA enzymes in the absence of KatG activation. IQG-607 given by the oral route to M. tuberculosis-infected mice reduced lung lesions. Experiments using early and late controls of infection revealed a bactericidal activity for IQG-607. HPLC and voltammetric methods were developed to quantify IQG-607. Pharmacokinetic studies showed short half-life, high clearance, moderate volume of distribution, and low oral bioavailability, which was not altered by feeding. Safety and toxic effects of IQG-607 after acute and 90-day repeated oral administrations in both rats and minipigs showed occurrence of mild to moderate toxic events. Eight multidrug-resistant strains (MDR-TB) were resistant to IQG-607, suggesting an association between katG mutation and increasing MIC values. Whole genome sequencing of three spontaneous IQG-607-resistant strains harbored katG gene mutations. MIC measurements and macrophage infection experiments with a laboratorial strain showed that katG mutation is sufficient to confer resistance to IQG-607 and that the macrophage intracellular environment cannot trigger the self-activation mechanism. Reduced activity of IQG-607 against an M. tuberculosis strain overexpressing S94A InhA mutant protein suggested both the need for KatG activation and InhA as its target. Further efforts are suggested to be pursued towards attempting to translate IQG-607 into a chemotherapeutic agent to treat tuberculosis.